Respiratory Syncytial Virus Associated Myocarditis Requiring Venoarterial Extracorporeal Membrane Oxygenation - Anamaria Milas; Aditya Shah; Neesha Anand; Meghan Saunders-Kurban; Samir Patel (Case Reports in Infectious Diseases)
Severe fulminant myocarditis causing cardiogenic shock can be a rapidly progressing, life threatening condition. Respiratory syncytial virus (RSV) is a very rare infectious culprit infrequently described in medical literature as a cause of myocarditis, particularly in adults. We present a case of acute fulminant myocarditis in a patient with PCR positive RSV infection requiring venoarterial extracorporeal membrane oxygenation (VA-ECMO).